Temnopleurus reevesii as a new sea urchin model in genetics. (5th January 2022) - Yaguchi, Shunsuke; Yaguchi, Junko
Abstract: Echinoderms, including sea urchins and starfish, have played important roles in cell, developmental and evolutionary biology research for more than a century. However, since most of them take a long time to mature sexually and their breeding seasons are limited, it has been difficult to obtain subsequent generations in the laboratory, resulting in them not being recognized as model organisms in recent genetics research. To overcome this issue, we maintained and obtained gametes from several nonmodel sea urchins in Japan and finally identified Temnopleurus reevesii as a suitable model for sea urchin genetics. Genomic and transcriptomic information was obtained for this model, and the DNA database TrBase was made publicly available. In this review, we describe how we found this species useful for biological research and show an example of CRISPR/Cas9 based knockout sea urchin. Abstract : Early development of T .  reevesii . They are transparent and have temperature tolerance.